Organizational change theory: Implications for health promotion practice - Batras, D.; Duff, Cameron; Smith, B. (Oxford University Press, 2016)
Sophisticated understandings of organizational dynamics and processes of organizational change are crucial for the development and success of health promotion initiatives. Theory has a valuable contribution to make in understanding organizational change, for identifying influential factors that should be the focus of change efforts and for selecting the strategies that can be applied to promote change. This article reviews select organizational change models to identify the most pertinent insights for health promotion practitioners. Theoretically derived considerations for practitioners who seek to foster organizational change include the extent to which the initiative is modifiable to fit with the internal context; the amount of time that is allocated to truly institutionalize change; the ability of the agents of change to build short-term success deliberately into their implementation plan; whether or not the shared group experience of action for change is positive or negative and the degree to which agencies that are the intended recipients of change are resourced to focus on internal factors. In reviewing theories of organizational change, the article also addresses strategies for facilitating the adoption of key theoretical insights into the design and implementation of health promotion initiatives in diverse organizational settings. If nothing else, aligning health promotion with organizational change theory promises insights into what it is that health promoters do and the time that it can take to do it effectively.